2011
DOI: 10.1074/jbc.m110.200774
|View full text |Cite
|
Sign up to set email alerts
|

The Stilbenoid Tyrosine Kinase Inhibitor, G6, Suppresses Jak2-V617F-mediated Human Pathological Cell Growth in Vitro and in Vivo

Abstract: Using structure-based virtual screening, we previously identified a novel stilbenoid inhibitor of Jak2 tyrosine kinase named G6. Here, we hypothesized that G6 suppresses Jak2-V617F-mediated human pathological cell growth in vitro and in vivo. We found that G6 inhibited proliferation of the Jak2-V617F expressing human erythroleukemia (HEL) cell line by promoting marked cell cycle arrest and inducing apoptosis. The G6-dependent increase in apoptosis levels was concomitant with increased caspase 3/7 activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…Interestingly, examination of the lungs, livers, and kidneys from these same animals found no fibrosis whatsoever, suggesting that the increased fibrosis in the G6 treated mice was a tumor-specific event. Consistent with this observation that G6 does not promote host organ fibrosis is a previous work where we reported that a 30 day administration of G6 into C57BL/6 mice did not produce any histological abnormalities, such as fibrosis, within the hearts, brains, kidneys, or lungs of the treated animals [14]. However, fibrosis within host tissues and tumor tissue is quite different and it is still unclear whether increased tumor fibrosis is advantageous or deleterious to the survival of the animal [31], [32].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, examination of the lungs, livers, and kidneys from these same animals found no fibrosis whatsoever, suggesting that the increased fibrosis in the G6 treated mice was a tumor-specific event. Consistent with this observation that G6 does not promote host organ fibrosis is a previous work where we reported that a 30 day administration of G6 into C57BL/6 mice did not produce any histological abnormalities, such as fibrosis, within the hearts, brains, kidneys, or lungs of the treated animals [14]. However, fibrosis within host tissues and tumor tissue is quite different and it is still unclear whether increased tumor fibrosis is advantageous or deleterious to the survival of the animal [31], [32].…”
Section: Discussionsupporting
confidence: 91%
“…G6 is a preclinical Jak kinase inhibitor with a Jak selectivity profile of Jak2>Jak3>>Jak1>>>Tyk2 [20]. The STAT selectivity profile for this compound is STAT5>STAT3>STAT1, and its principal mechanism of action is induction of apoptosis [21]. Figure 3A shows the ABT737 predictive simulation results indicting a dose-dependent decrease on HEL cell viability, while Figure 3B shows the validation of these results on cultured cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the Jak2-V617F mutation activates multiple anti-apoptotic proteins, including MCL1. Inhibition of Jak2 by G6 inhibits MCL1 via downstream inhibition of its transcription factors [21] and therefore contributes further to enhancing induction of apoptosis and reducing tumor cell viability. This also addresses the possible resistance mechanism that can arise when MCL1 expression increases subsequent to BCL2 inhibition [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…HEL92.1.7 cell line, deriving from acute erythroid leukemia (AML M6) is homozygous for the V617F mutation, which induces constitutive JAK2 phosphorylation and drives HEL92.1.7 cell proliferation (Kirabo et al, 2011;Quentmeier et al, 2006). SET-2 cells, deriving from essential thrombocythemia with AML transformation, were confirmed to be heterozygotic for the V617F mutation (NovotnyDiermayr et al, 2012).…”
Section: Reference Genes For Gene Expression Analysis Are Different Fmentioning
confidence: 94%